Oracle API Management 12c implementation : learn how to successfully implement API management using Oracle's API Management Solution 12c - Weir, Luis Augusto (Professional expertise distilled., 2015)
Learn how to successfully implement API management using Oracle's API Management Solution 12c About This Book Explore the key concepts, goals, and objectives of API Management and learn how to implement it using the Oracle API Management Solution Understand the concepts and objectives of the Application Service Governance (ASG), along with the governance framework that encompasses people, processes, and technology Get to grips with API Management readiness assessments, gap analysis, digital reference architecture, and implementation roadmaps Who This Book Is For This book is for Enterprise Architects, Solution Architects, Technical Architects, and SOA and API consultants who want to successfully implement API Management using the Oracle API Management Solution products. What You Will Learn Understand how to manage a set of APIs Discover the differences and similarities between API Management and SOA Governance, and where and how these two disciplines converge into Application Services Governance (ASG) Grasp information about ASG and how to define an ASG governance framework Understand the challenges for organizations looking to expose APIs to the external world. Identify common scenarios and how to solve them Define an Oracle API management deployment topology Install and configure Oracle API Catalog (OAC), Oracle API Manager (OAPIM), and Oracle API Gateway (OAG) Learn about API subscriptions and API community management with the OAPIM portal Implement Oracle API Manager (OAPIM) including creation, publishing, management and deprecation of APIs In Detail Oracle SOA Governance is a comprehensive, service-orientated governance solution that is designed to make the transition to SOA easier. API management is the discipline that governs the software development lifecycle of APIs. It defines the tools and processes needed to build, publish and operate APIs including the management of the community of developers around it. This book illustrates how to successfully implement API Management in your organization. To achieve this, the importance of defining an API management strategy and implementation roadmap so that capabilities are implemented in the right order and timeframes is described. It starts by describing all of the fundamental concepts around API Management and related disciplines such as SOA Governance and DevOps in order to dispel the confusion surrounding these topics. The book then takes you on the journey of implementing API Management...